Analysis of the effect of ENSO and IOD on the productivity of yellowfin tuna (Thunnus albacares) in the South Indian Ocean, East Java, Indonesia - ABU BAKAR SAMBAH; AURUM NOOR’IZZAH; CANDRA ADI INTYAS; DENNY WIDHIYANURIYAWAN; DIDIET POERNAWAN AFFANDY; ADI WIJAYA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Sambah AB, Noor’izzah A, Intyas CA, Widhiyanuriyawan D, Affandy DP, Wijaya A. 2023. Analysis of the effect of ENSO and IOD on the productivity of yellowfin tuna (Thunnus albacares) in the South Indian Ocean, East Java, Indonesia. Biodiversitas 24: 2689-2700. Yellowfin tuna (Thunnus albacares) is one of the fish that migrates through the Indian Ocean and is primarily caught in the south Java waters which are directly adjacent to the Indian Ocean. Fish abundance and migration are influenced by oceanographic factors, including climatic factors which affect annual and interannual variations, such as the Indian Ocean Dipole (IOD) and the El Nino Southern Oscillation (ENSO). This study aimed to determine the effect of climate anomalies on the productivity of yellowfin tuna in the Indian Ocean south of East Java, Indonesia. Data collection was carried out at Coastal Fishing Port of Pondokdadap East Java, involving 58 respondents consisting of fishermen with yellowfin tuna catches. The boundaries of the research area are at coordinates 110.9°-114.5° East Longitude and 8°-11° South Latitude. The data used in the analysis consisted of Sea Surface Temperature (SST) data, chlorophyll-a data, Nino 3.4 data, Dipole Mode Index (DMI) data, and yellowfin tuna catch data for the year 2017-2021. The results showed that of the fifteen GAM models, the combination of variables that most affected fish productivity was the distribution of chlorophyll-a and the ENSO phenomenon with values ??of AIC (1503.33) and DE (64.30%). Pearson correlation analysis showed that the IOD phenomenon was influenced by SST and chlorophyll-a, while SST and chlorophyll-a did not significantly influence the ENSO phenomenon. These results indicated that the phenomenon of climate anomalies and the oceanographic conditions in the waters indirectly affect fish productivity through the food chain process.